Implementation of Practice-Oriented Training as the Basis of Developing Students' Communicative Competence - Kenjayeva Diana Shermatovna (Research Parks Publishers, 2022)
The successful implementation of the functions of practice-oriented learning in the system of vocational education requires the study of the theoretical and methodological basis, which is the most important attribute of any pedagogical system. The author of the article proposes to use interdisciplinary, contextual, modular approaches in the educational process to solve this problem, and also substantiates the need to consider them in unity. In addition, we showed a practice-oriented approach not only in solving a problem using the example of a specialized discipline, but also showed the possibility of implementation of practice-oriented training as the basis of developing students' communicative competence.